A Tug of War Team Contest - Samuel Häfner (University of Basel, Center of Business and Economics (WWZ), 2015)
This paper analyzes a tug of war contest between two teams. In each round of the tug of war a pair of agents from the opposing teams competes in a private value all-pay auction with asymmetric type distributions and effort effectiveness. Whichever team arrives fi rst at a given lead in terms of battle victories over the opponent wins the tug of war. There exists a unique Markov-perfect equilibrium in bidding strategies that depend on the player's valuation and on the history through the current state of the tug of war only. We derive rich comparative statics for this equilibrium by using the fact that the states of the tug of war evolve according to a time-homogeneous absorbing Markov chain.
Keywords: D74; F51; H56; 330; Team Contests; Multi-Stage Contests; Tug of War; All-Pay Auction; Absorbing Markov Chain